2020
DOI: 10.1007/s12079-020-00575-2
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa induce transcriptomic alterations in bovine oviductal epithelial cells prior to initial contact

Abstract: The capability of spermatozoa to directly influence maternal gene expression is already established. Indeed, some of the changes induced by spermatozoa may have a direct functional importance in the pre-conceptional period. Although the mechanisms underlying these sperm-maternal interactions are not well characterized, it is possible that they could involve ligands that are released from the spermatozoa. This study therefore aimed to test whether physical contact between bovine spermatozoa and bovine oviductal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Frozen semen straws from three different bulls were processed separately following the methods described by our group previously [ 36 ]. In brief, frozen semen straws (4 straws from each bull) were thawed at 37 °C and the contents of the straws were layered over 4 mL of 60% isoosmotic Percoll ® solution (GE Healthcare, 17-0891-02, Vendevägen, Sweden) Subsequently, the overlayered semen samples were centrifuged at 300× g for 20 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen semen straws from three different bulls were processed separately following the methods described by our group previously [ 36 ]. In brief, frozen semen straws (4 straws from each bull) were thawed at 37 °C and the contents of the straws were layered over 4 mL of 60% isoosmotic Percoll ® solution (GE Healthcare, 17-0891-02, Vendevägen, Sweden) Subsequently, the overlayered semen samples were centrifuged at 300× g for 20 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…It appears logical to state that the SP is a composite secretion that promotes cell-to-cell communication between reproductive and non-reproductive cells, following evidence from experimental studies in vivo (Alvarez-Rodriguez et al, 2019a;2020a) and in vitro (Reshi et al, 2020). Of interest, however, is to insist in the fact that sEVs are, at least in vitro (Bai et al, 2018), able to elicit specific changes in the lining epithelium.…”
Section: Seminal Extracellular Vesicles and Their Role In The Spmentioning
confidence: 99%
“…Studies showed that EVs produced from the male reproductive tract, including epididymosomes and prostasomes, play vital roles in the maturation process of spermatozoa (Saez et al, 2003; Wu et al, 2017). Spermatozoa undergo several physical and biochemical changes during their journey towards oocyte starting from the anterior vagina after coitus (Reshi et al, 2020). These modifications possibly occur due to the crosstalk between the spermatozoa and the female reproductive tract leading to functional maturation.…”
Section: The Role Of Evs In Male Gamete Maturationmentioning
confidence: 99%